1999
DOI: 10.1063/1.479181
|View full text |Cite
|
Sign up to set email alerts
|

On the origin and contribution of the diamagnetic term in four-component relativistic calculations of magnetic properties

Abstract: The relativistic Dirac Hamiltonian that describes the motion of electrons in a magnetic field contains only paramagnetic terms ͑i.e., terms linear in the vector potential A͒ while the corresponding nonrelativistic Schrödinger Hamiltonian also contains diamagnetic terms ͑i.e., those from an A 2 operator͒. We demonstrate that all diamagnetic terms relativistically arise from second-order perturbation theory and that they correspond to a ''redressing'' of the electrons by the magnetic field. If the nonrelativisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
195
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(202 citation statements)
references
References 25 publications
4
195
1
Order By: Relevance
“…1,2 The first ones 1 were obtained within the Sternheim approximation. 3 It has been shown formally 4,5 that the diamagnetic component of magnetic properties is only recovered in the nonrelativistic limit when electron-positron rotations are taken into account. Therefore in the four-component linear-response theory the paramagnetic term is identified with the linear-response related to electron-electron rotations, while the diamagnetic one is identified with the contribution associated to electronpositron rotations.…”
Section: Formal Relations Connecting Different Approaches To Calculatmentioning
confidence: 99%
“…1,2 The first ones 1 were obtained within the Sternheim approximation. 3 It has been shown formally 4,5 that the diamagnetic component of magnetic properties is only recovered in the nonrelativistic limit when electron-positron rotations are taken into account. Therefore in the four-component linear-response theory the paramagnetic term is identified with the linear-response related to electron-electron rotations, while the diamagnetic one is identified with the contribution associated to electronpositron rotations.…”
Section: Formal Relations Connecting Different Approaches To Calculatmentioning
confidence: 99%
“…The calculation of the propagator involves excitations to virtual electronic states (e-e excitations) and virtual positronic states (e-p excitations). Both kinds of terms can be obtained separately with adequate decomposition of the corresponding blocks of the propagator, 19,20 as implemented in the DIRAC 10 code. For the equilibrium molecular geometry, the first order electronic contribution and the nuclear contribution h (2)nuc ω,μ N can be gathered together in the simple (nuclear) term…”
Section: A Relativistic 4-component Expression Of the Spin-rotation mentioning
confidence: 99%
“…In the last few years an ever increasing number of new formalisms and calculations for the evaluation of relativistic effects on molecular properties from four-, two-, or onecomponent response schemes or perturbation theory approaches have been published. [1][2][3][4][5][6][7][8][9][10][11] It was shown that the inclusion of such effects in the calculation of some molecular properties is mandatory when one wants to reproduce experimental trends. 4,10 Relativistic spin-orbit ͑SO͒ effects on magnetic molecular properties were thought to be the most important ones until recent calculations of Visscher et al 4 Numerical results for nuclear magnetic shieldings obtained by four-component calculations and their counterpart from RayleighSchrödinger perturbation theory ͑RSPT͒ only match each other for the shielding of heavy atoms X in HX compounds when a new term different from SO is included.…”
Section: Introductionmentioning
confidence: 99%